Immunogenicity of Hepatitis B Vaccine in Pediatric Systemic Lupus Erythematosus Patients - Madaeng T. (2023)
Background: Pediatric patients with systemic lupus erythematosus (SLE) are at increased infectious risk caused by underlying immunologic dysregulation and immunosuppressive therapy. Hepatitis B virus (HBV) could be reactivated during the immunosuppressive treatment in patients with past HBV infections. Information on immunogenicity after hepatitis B (HB) immunization and reimmunization are still scarce. Methods: SLE patients 5-18 years of age who had completed a primary HB immunization were enrolled. Anti-HBs levels at enrollment and after each vaccine dose were determined. Patients with anti-HBs levels < 10 mIU/mL were administered 1 booster dose. After 1 booster dose, patients with negative anti-HBs levels were administered 2 more booster doses. Results: Ninety-three SLE patients were enrolled. The prevalence of seroprotection assessed by anti-HBs > 10 mIU/mL after completion of a primary HB immunization was 25.8% (95% CI: 17.2-34.4). Lupus nephritis was associated with unprotective anti-HBs levels [odds ratio (OR): 4.341; 95% CI: 1.044-18.040]. The anti-HBs seroconversion was 72.3% (95% CI: 61.5-83.0) after 1 booster dose and increased up to 93.4% (95% CI: 86.9-98.4) after 3 booster doses. SLE Disease Activity Index-2000 score ≥ 4 (OR: 4.625; 95% CI: 1.45-14.80) was significantly associated with nonseroconversion after the first booster dose. Hypocomplementemia before the first and second booster doses (OR: 27; 95% CI: 1.26-578.35) was significantly associated with nonseroconversion after 3 booster doses. Conclusions: All pediatric SLE patients should be evaluated for HBV serological status before immunosuppressive treatment. SLE patients with SLE Disease Activity Index-2000 score > 4 should need 3 booster doses if their anti-HBs level was < 10 mIU/mL.